ANALISIS PRINSIP PENGEMBANGAN MATERI (RELEVANSI, KONSISTENSI, ADEQUACY) DAN IMPLEMENTASI KMA NO 347 TAHUN 2022 PADA PELAJARAN AKIDAH AKHLAK KELAS 4-6 (STUDI KASUS DI MIN 1 YOGYAKARTA) - Rivaldi Darmawan; Muh Wasith Achadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article dialogues the results of the evaluation of the principles of material development (relevance, consistency and adequacy) and the implementation of learning akidah akhlak based on the Decree of the Minister of Religion (KMA) no 347 of 2022. It should be understood that KMA 347 is used as a guideline in implementing madrasah independent curriculum learning. As in implementing madrasah independent curriculum-based learning, it needs to require adaptation so that learning can proceed as desired. The research method used in this case is field research or field research with a qualitative approach. In addition to researchers analyzing the material of the moral creed textbook, researchers observed the learning process of moral creed in grades 4-6 at the Yogyakarta State Islamic Boarding School. The results of this study show the process and obstacles of MIN 1 Yogyakarta in implementing an independent curriculum. Time allocation in implementing differentiated learning and teacher readiness are still obstacles in implementing an independent curriculum. Evaluation of the material development principles of the book of moral creed for grades 4-6 found an imbalance in the division between the material of faith and morals. Some material is incomplete and there is repetition so that it does not comply with the principles of material development (Relevance, Consistency, and Adequacy).